سیرت نبوی ﷺ کے اخلاقی ضوابط کا بین الاقوامی اخلاقی فلسفوں سے تقابلی جائزہ: A Comparative Analysis of the Ethical Principles of the Prophet ﷺ and International Moral Philosophies (Contemporary Journal of Social Science Review, 2024)
This study undertakes a comprehensive comparative analysis of the ethical principles derived from the life and teachings of Prophet Muhammad ﷺ (Seerah) and various international moral philosophies, spanning classical Greek thought, medieval European ethics, and contemporary ethical frameworks such as Utilitarianism, Deontology, and Virtue Ethics. The research emphasizes the integration of wahy (divine revelation) and human reason in Islamic ethics, highlighting the centrality of intention (niyyah), moderation, and universal compassion (Rahmat al-Alamin) in moral deliberation. The study further explores the role of ethical praxis in shaping individual and societal conduct, contrasting the Prophet’s ﷺ ethical framework with Western philosophical notions of morality that often separate theory from practice. By examining concepts such as moral universality, justice, human dignity, and spiritual and societal well-being, this paper elucidates the applicability of Prophetic ethics in addressing contemporary moral crises, including relativism, hedonism, and moral ambiguity. The findings suggest that the ethical system exemplified in the Seerah provides a holistic paradigm for moral philosophy, integrating individual spiritual development, societal justice, and global human welfare, thereby offering a substantive contribution to cross-cultural moral discourse.